2-[(1,3-Benzodioxol-5-ylmethylidene)amino]-4,5,6,7-tetrahydro-1-benzothiophene-3-carbonitrile - Abdullah M. Asiri; Salman A. Khan; M. Nawaz Tahir (Acta Crystallographica Section E, 2011)
The title compound, C17H14N2O2S, crystallizes with two roughly planar molecules in the asymmetric unit, in which the dihedral angles between the 1,3-benzodioxole-5-carbaldehyde moiety and the heterocyclic five-membered ring are 3.76 (5) and 5.33 (12)°. In each molecule, a short C—H...S contact generates an S(5) ring. In the crystal, pairs of molecules are linked by a weak C—H...N interaction, forming dimers.